IMPLEMENTASI TERAPI BERMAIN MEWARNAI PADA ANAK DHF (DENGUE HEMORAGIC FEVER) YANG MENGALAMI KECEMASAN DI RUMAH SAKIT TK II PUTRI HIJAU MEDAN - Putri Khairani; Purwaningsih Purwaningsih; Nisrina Nisrina (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2025)
Dengue Hemorrhagic Fever (DHF) is an acute illness caused by a viral infection transmitted by Aedes aegypti mosquitoes. It affects all age groups and is characterized by high fever lasting 4-7 days, bleeding manifestations, and thrombocytopenia. Children with DHF often exhibit signs of anxiety such as crying, fear, anger, and refusal to eat during hospitalization. One intervention that can be used to reduce anxiety is play therapy. This study aims to describe the implementation of coloring play therapy in children with DHF who experience anxiety during hospitalization at RS TK II Putri Hijau Medan. This research employed a descriptive case study method involving two children who experienced severe anxiety based on the Faces Anxiety Scale (FIS) with a score of 5. The intervention consisted of coloring play therapy administered over three consecutive days, with each session lasting 15-30 minutes. The results showed a reduction in anxiety levels in both clients. Client I showed a decrease from FIS scale 5 (severe anxiety) to FIS scale 2 (no anxiety), while Client II showed a decrease from FIS scale 5 (severe anxiety) to FIS scale 1 (very calm). These findings indicate that coloring play therapy is effective in reducing hospitalization-related anxiety in children with DHF. It is recommended that this therapy be routinely applied to children experiencing mild to severe anxiety, both in hospital and home settings.